DIGITAL TRANSFORMATION IN THE MANAUS INDUSTRIAL HUB: INCREASED EFFICIENCY IN THE PRODUCTION OF LITHIUM BATTERIES THROUGH INDUSTRY 4.0 - Damasceno, Alexandre Holanda; Leite, Jandecy Cabral; Junior, Jorge de Almeida Brito; Júnior, Fernando Cardoso de Queiroz (Seven Editora, 2024)
The lithium battery industry faces increasing challenges in terms of demand and expectations for sustainability and efficiency. In the context of the Manaus Industrial Pole, this study explores the application of Industry 4.0 technologies to overcome these challenges and increase production efficiency. The research implemented integrated cyber-physical systems, advanced automation, and real-time data analysis on a lithium battery assembly line, replacing manual processes with automated solutions. The results demonstrated a significant improvement in production accuracy and speed, with a 40% reduction in cycle time and a 75% decrease in product rejection rate, highlighting the potential of digitalization to optimize industrial operations and meet the demands of a competitive global market. This study contributes to the literature on digital transformation in manufacturing, offering practical insights into the implementation of emerging technologies in complex industrial environments. DOI:https://doi.org/10.56238/sevened2024.037-098